2021
DOI: 10.3389/fpubh.2021.679254
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology Characteristics of COVID-19 Infection Amongst Primary Health Care Workers in Qatar: March-October 2020

Abstract: Background: COVID-19 transmission was significant among Healthcare workers worldwide. In March 2020, Qatar started reporting numbers of COVID-19 positive cases among workers in Primary Health Care Corporation (PHCC). The study estimates the burden of the aforementioned infections and examines the demographic characteristics associated with the recorded positivity rates.Method: A cross-sectional descriptive study was conducted among Primary healthcare workers between March 1st and October 31st, 2020. The study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
0
20
0
3
Order By: Relevance
“…Protection conferred by PPE was mainly studied for Influenza, Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS), but evidence is controversial for COVID-19 [ [11] , [12] , [13] ]. Moreover, very few data have been published on HCWs in long-term care facilities (LTCFs) and primary care [ 14 , 15 ], despite intense involvement in the pandemic response. Most studies focused on the hospital setting, although exposures, organization of care and access to infection prevention and control (IPC) expertise vary greatly across facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Protection conferred by PPE was mainly studied for Influenza, Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS), but evidence is controversial for COVID-19 [ [11] , [12] , [13] ]. Moreover, very few data have been published on HCWs in long-term care facilities (LTCFs) and primary care [ 14 , 15 ], despite intense involvement in the pandemic response. Most studies focused on the hospital setting, although exposures, organization of care and access to infection prevention and control (IPC) expertise vary greatly across facilities.…”
Section: Introductionmentioning
confidence: 99%
“…PPE-conferred protection was mainly studied for Influenza, Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS), but evidence is controversial for COVID-19 [11][12][13]. Moreover, very few data have been published on HCWs in long-term care facilities (LTCFs) and primary care [14,15], despite their intense involvement in the pandemic response. Most studies focused on the hospital setting, although exposures, organization of care and access to infection prevention and control (IPC) expertise vary greatly across facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Although ancillary staff made up of approximately 10% of primary HCW cases in the current study, these figures are also likely an underestimate as many articles do not specify the type of HCWs and consider occupational roles as either doctors, nurses and "other" healthcare staff. An increasing number of epidemiological studies have also reported not only a greater risk of infection but also highlighted ancillary staff as the main affected group within their cohorts [46][47][48][49][50][51] (Table 2). Several factors could explain increased propensity of ancillary staff to infection.…”
Section: Discussionmentioning
confidence: 99%